A study of visual perception: Social anxiety and virtual realism - Kwon, J; Chalmers, A; Czanner, S; Czanner, G; Powell, J (2009)
Virtual reality exposure therapy offers the possibility of tackling social anxiety in an efficient, safe and controlled manner. A key question, however, is what is the level of realism required in virtual environments to ensure the environment is effective in helping the participant to deal with their anxiety. One concern which affects a lot of people from all walks of life is the fear of a job interview. In this paper we investigate the relationship between anxiety and varying levels of realistic fidelity. We recruited 60 volunteers and studied their anxiety levels via randomised block design, where each block was exposed to a different level of fidelity of the virtual avatars: realistic 3D human avatar, cartoon-like 3D avatar, and human photographs. We measured the social anxiety of all participants via a measure of eyes avoidance behaviour. Our main findings are that the participants exhibited more anxiety in accordance with the attitude of virtual avatars than the avatar's level of realism. Copyright © 2009 by the Association for Computing Machinery Inc.